SARS-CoV-2 Infection in Spondyloarthritis Patients Treated With Biotechnological Drugs: A Study on Serology - Ortolan, Augusta; Lorenzin, Mariagrazia; Cosma, Chiara; Cozzi, Giacomo; Padoan, Andrea; Doria, Andrea; Plebani, Mario; Ramonda, Roberta (Frontiers in Immunology, 2021)
Objective: serology could help to define the real extent of SARS-CoV-2 diffusion, especially in individuals considered at higher risk of COVID-19, such as spondiloarthritis (SpA) patients undergoing immunosuppressant. Our aim was to detect, by serology, previous SARS-CoV-2 contact in SpA, compared to health care workers (HCW), and healthy controls. Methods: Sera from consecutive patients affected by SpA undergoing cytokine-targeted therapy, HCW and healthy controls from 2015 were analysed through chemiluminescent analytical system for the presence of IgG and IgM anti-SARS-CoV-2. Positive patients (IgM or IgG, or both) additionally underwent real-time Polymerase-Chain-Reaction (RT-PCR) to test for active infection. Serology was repeated at 3-months in SpA. Data across 3 groups were compared by Kruskal Wallis/Chi-square, and between 2 groups by Wilcoxon rank test/Chi-Square. P≤0.05 were considered significant. Results: 200 SpA, 95 HCW and 101 controls were recruited. Positive serology was found in 25(12.5%) SpA, 8(8.4%) HCW, 0(0%) controls (p=0.001). SpA patients with positive serology more frequently reported COVID-19-like symptoms than those with negative serology (20% vs 4%, p=0.009) and 2 had COVID-19 as confirmed by RT-PCR, none severe. No HCW reported symptoms or had positive RT-PCR. In SpA patients, at 3 months, mean IgM titres decreased from 2.76±2.93 to 2.38±2.95 (p=0.001), while IgG titres from 0.89±3.25 to 0.31±0.87 (p=ns). Conclusions: serology revealed that exposure to SARS-CoV-2 in SpA patients and HCW was higher than expected based on reported symptoms. In SpA, anti-cytokine therapy could act as a protective factor for a severe disease course. However, a serocoversion was not observed at 3-months.